Confronting Islamophobia in a Rural Appalachian Classroom. (3rd April 2018) - Shepherd, Samuel Troy
Abstract : A research study in West Virginia in which a series of lessons were created to address the issues of Islamophobia, American exceptionalism, and nativism within a seventh-grade Ancient Civilizations classroom. The lessons spotlighted the Middle East, and students were presented with a more realistic view of Islamic cultures and were able to interact with Muslim individuals. Lessons focused on achieving authentic human interaction, seeing through multiple perspectives, and appreciating the differences in other cultures. Students were confronted with experiences and content that allowed them to challenge their xenophobic sentiments. These experiences had profound effects on students' negative and xenophobic dispositions.